Serum metabolic changes associated with dioxin exposure in a Chinese male cohort. (October 2020) - Liang, Yanshan; Tang, Zhi; Jiang, Yousheng; Ai, Chunyan; Peng, Jinling; Liu, Yuan; Chen, Jinru; Zhang, Jianqing; Cai, Zongwei
Graphical abstract: Highlights: Serum metabolic perturbations by dioxin exposure in humans were investigated. Suppression of fatty acid β-oxidation associated with liver diseases was observed. Changes of metabolites in pathways related to inflammation were observed. Metabolic alternations associated with cardiovascular diseases was observed. Abstract: Dioxins, a group of persistent organic pollutants, have been proved to correlate with ranges of diseases by activating the aryl hydrocarbon receptor (AhR). However, previous dioxin toxicity studies primarily focused on the activation of AhR with signaling pathways at gene and protein levels. The investigation of underlying mechanisms at the metabolic level is still necessary. In this study, serum samples of 48 and 47 healthy participants with the highest and lowest dioxin levels based on quartile distribution of the serum dioxin concentrations of 215 male adults were selected for metabolomics analysis by using liquid chromatography coupled with orbitrap high-resolution mass spectrometry to investigate dioxin-related metabolic responses. The identified potential biomarkers included acylcarnitines, fatty acids and derivatives, glycerophospholipids, etc. suggested that metabolic pathways such as fatty acid β-oxidation, essential fatty acid metabolism, arachidonic acid metabolism, glycerophospholipid and sphingolipid metabolism and purine metabolism were disturbed by dioxin exposure. The results indicated that people with high dioxin exposure levels were at the potential health risks of inflammation, liver and cardiovascular diseases. The metabolic findings may help understand the link between dioxin exposure and the diseases.